The Use of a Diagnostic Matrix in the Management of the Severely Worn Dentition - Phuong D. Doan, DDS;1 and Gary R. Goldstein, DDS2 (Journal of Prosthodontics, 2007)
The management of the interim phase of a complete oral rehabilitation in patients with severely worn dentition is often challenging due to loss of occlusal vertical dimension, loss of tooth structure, uneven wear of teeth creating an uneven plane of occlusion, and para-functional habits.